Stratification of patients with type 2 diabetes mellitus for painless ischemic heart disease - Natalya Ivanovna Volkova; Andrey Vladimirovich Kharakhashyan; Yulia Alekseevna Sorokina; Il'ya Yur'evich Davidenko (Сахарный диабет)
Aims. Development of assessment model for type 2 diabetes mellitus (DM) patient stratification for painless ischemic heart disease(IHD). Materials and methods. 258 patients with DM type 2 participated in this study (109 male and 149 female) of mean age 58.4?8.5 withDM experience of 7.9?6.1 years. All participants were subdivided into three groups: first - DM type 2 without history of painless IHD(138 individuals); second - DM type 2 with diagnosed painless IHD (50 individuals); third - DM type 2 with painful myocardialischemia. We assessed "classic" risk factors for IHD, immediately connected with DM comorbidity, as well as "additional" risk factors,potentially capable of provoking both painless and painful IHD. In addition, we screened our patients for structural abnormalitiesof heart by means of echocardiography. Painless IHD was diagnosed by treadmill-tests or Holter monitoring with submaximal exercise.Accumulated data was statistically processed with the use of Spearman's rank correlation, as well as binary logistic regression method.Results were deemed statistically significant at р